Mechanisms and control measures of low temperature storage-induced chilling injury to solanaceous vegetables and fruits - Yuan, Qi; Jiang, Yaqin; Yang, Qihong; Li, Weiliu; Gan, Guiyun; Cai, Liangyu; Li, Wenjia; Qin, Chunchun; Yu, Chuying; Wang, Yikui (Frontiers in Plant Science, 2024)
Low temperature storage is widely used for storage and transportation of fruits and vegetables after harvest. As a cold-sensitive fruit vegetable, post-harvest solanaceous vegetables and fruits are susceptible to chilling injury during low temperature storage, which reduces its sensory quality and edible quality and shortens its storage period, thus leading to huge economic losses. Therefore, it is an essential to clarify the occurrence mechanism of chilling injury caused by low temperature storage in solanaceous vegetables and fruits, and to propose corresponding prevention and control measures for chilling injury. In recent years, a series of progress has been made in the research on chilling injury prevention and control and low temperature stress tolerance of solanaceous vegetables and fruits. This paper describes the chilling injury symptoms of postharvest solanaceous vegetables and fruits, clarifies the physiological and biochemical mechanisms in the chilling injury process, the molecular mechanisms, and prevention and control measures, and summarizes the latest research advancements on chilling injury and chilling tolerance regulation of solanaceous vegetables and fruits, which can provide valuable references for low temperature storage and chilling injury prevention and control measures of solanaceous vegetables and fruits.